Site directed Mutagenesis of Carbohydrate Binding Module Family 40 (CBM40) domain from Vibrio cholerae Non-01 sialidase - Nadiawati, Alias; Noor Asidah, Mohamed; Gogula Selvi, Asang (2021)
The location of sialic acid at the termini of various carbohydrate complexes often exploited by microbial pathogens (influenza and parainfluenza viruses) to bind and gain entry to the host cell during the initial stages of pathogenesis thus mediating specific role in human health and diseases. Carbohydrate-binding modules (CBMs) help target the main enzyme to appropriate substrates and increase their catalytic efficiency. However, proteins with weak binding affinity often use site-directed mutagenesis approach to enhance protein affinity via an avidity effect. In this study, a wild-type Family 40 Carbohydrate Binding Module (WT-CBM40) was genetically modified by site-directed mutagenesis to form a stable mutant CBM40 (M-CBM40) to improve domain affinity towards sialic acid. In this study, a gene encoding for Family 40 Carbohydrate Binding Module (CBM40) from Vibrio cholerae Non-O1 sialidase was cloned in pET22b(+) and successfully expressed in E. coli BL21 (DE3) strain. The CBM40 encodes for 195 amino acids with 585 bp of nucleotide sequence. Mutation of Thr200 to Asn200 was successfully performed using the QuikChange II Site-Directed Mutagenesis Kit (Agilent). This study also deals with the generation of a 3-D model of the mutant CBM40 with 2w68.1.A as a template. The validation of mutant CBM40 brings to 0.99 Global Model Quality Estimation (GMQE) scores and 1.14 Quality Model Energy Analysis (QMEAN) Z-scores. Both results indicate the reliability of the mutant model. The analysis visualization of mutant CBM40 by UCSF Chimera proved by MatchMaker sequence alignment score of 1005.9 and RMSD score of 0.08 Å demonstrated both wild type CBM40 and mutant CBM40 structure were closely related. The results gained by Arpeggio web server revealed that the affinity of mutant CBM40 higher than wild type CBM40. For the protein expression study, mutant CBM40 was successfully expressed at 25 ˚C when induced with 1 mM IPTG whereas for wild-type CBM40 was successfully expressed at 18 ˚C, the best IPTG concentration used was 1.5 mM. Maximum expression was achieved at 20 hours after post-induction time. SDS-PAGE analysis of the expressed wild-type and mutant CBM40 proteins displayed a protein band with a molecular mass of 21 kDa. This contruct has a big potential to be developed as therapeutics agent especially as biologics to prevent harmful pathogens gain entry through sialic acid binding present on human and mammalian cell surfaces The optimum characterization conditions established would further lead to the discovery of the true potential of CBM40 protein in enhancing substrate binding affinity, protein-carbohydrate recognition which underpins its broad applications in biotechnology and protein engineering fields.